2021
DOI: 10.3390/v13081595
|View full text |Cite
|
Sign up to set email alerts
|

Plant-Produced Glycosylated and In Vivo Deglycosylated Receptor Binding Domain Proteins of SARS-CoV-2 Induce Potent Neutralizing Responses in Mice

Abstract: The COVID-19 pandemic, caused by SARS-CoV-2, has rapidly spread to more than 222 countries and has put global public health at high risk. The world urgently needs cost-effective and safe SARS-CoV-2 vaccines, antiviral, and therapeutic drugs to control it. In this study, we engineered the receptor binding domain (RBD) of the SARS-CoV-2 spike (S) protein and produced it in the plant Nicotiana benthamiana in a glycosylated and deglycosylated form. Expression levels of both glycosylated (gRBD) and deglycosylated (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
76
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(85 citation statements)
references
References 79 publications
(134 reference statements)
9
76
0
Order By: Relevance
“…This has also been combined with the co-expression of human furin to support proteolytic processing in planta , where this would not otherwise occur ( Margolin et al, 2020c ). The impetus behind these approaches is to produce recombinant viral glycoproteins in as close to their native conformation as possible and while many promising plant-derived SARS-CoV-2 vaccine candidates have been reported these have mostly focused on the receptor binding domain ( Rattanapisit et al, 2020 ; Maharjan et al, 2021 ; Mamedov et al, 2021 ; Shin et al, 2021 ) or chimaeric spike-derived antigens ( Ward et al, 2021 ) rather than a native spike that recapitulates the virion-associated glycoprotein structure.…”
Section: Introductionmentioning
confidence: 99%
“…This has also been combined with the co-expression of human furin to support proteolytic processing in planta , where this would not otherwise occur ( Margolin et al, 2020c ). The impetus behind these approaches is to produce recombinant viral glycoproteins in as close to their native conformation as possible and while many promising plant-derived SARS-CoV-2 vaccine candidates have been reported these have mostly focused on the receptor binding domain ( Rattanapisit et al, 2020 ; Maharjan et al, 2021 ; Mamedov et al, 2021 ; Shin et al, 2021 ) or chimaeric spike-derived antigens ( Ward et al, 2021 ) rather than a native spike that recapitulates the virion-associated glycoprotein structure.…”
Section: Introductionmentioning
confidence: 99%
“…Since the S protein of SARS-CoV, MERS-CoV, and SARS-CoV-2 contains neutralizing epitopes, it has been shown to be a leading candidate for vaccine developments. In this regard, a number of studies demonstrated that the S protein induced potent humoral and cellular immune responses in tested animal models [1][2][3][4][5]. Most COVID-19 vaccines, which are currently approved or under development (mRNA, DNA, viral vector-based, subunits, and protein-based vaccine) were designed and developed on the basis of the S protein [4][5][6][7][8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…In this regard, a number of studies demonstrated that the S protein induced potent humoral and cellular immune responses in tested animal models [1][2][3][4][5]. Most COVID-19 vaccines, which are currently approved or under development (mRNA, DNA, viral vector-based, subunits, and protein-based vaccine) were designed and developed on the basis of the S protein [4][5][6][7][8][9][10][11]. The genome size of SARS-CoV-2 is ~30 kb, one-third of which encodes the S (spike), N (nucleocapsid), E (envelop), and M (matrix) structural proteins.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…ERUCoV-VAC-specific neutralizing antibody was identified using a microneutralization test (MNT) as described previously [29]. The titre of the neutralising antibody was determined as the highest dilution of serum at which the infectivity was neutralised in 50% of the cells in the wells.…”
Section: Micro Neutralization Test (Mnt)mentioning
confidence: 99%